An animal experimental study of porous magnesium scaffold degradation and osteogenesis - Liu,Y.J. (2014)
Our objective was to observe the biodegradable and osteogenic properties of magnesium scaffolding under in vivo conditions. Twelve 6-month-old male New Zealand white rabbits were randomly divided into two groups. The chosen operation site was the femoral condyle on the right side. The experimental group was implanted with porous magnesium scaffolds, while the control group was implanted with hydroxyapatite scaffolds. X-ray and blood tests, which included serum magnesium, alanine aminotransferase (ALT), creatinine (CREA), and blood urea nitrogen (BUN) were performed serially at 1, 2, and 3 weeks, and 1, 2, and 3 months. All rabbits were killed 3 months postoperatively, and the heart, kidney, spleen, and liver were analyzed with hematoxylin and eosin (HE) staining. The bone samples were subjected to microcomputed tomography scanning (micro-CT) and hard tissue biopsy. SPSS 13.0 (USA) was used for data analysis, and values of P<0.05 were considered to be significant. Bubbles appeared in the X-ray of the experimental group after 2 weeks, whereas there was no gas in the control group. There were no statistical differences for the serum magnesium concentrations, ALT, BUN, and CREA between the two groups (P>0.05). All HE-stained slices were normal, which suggested good biocompatibility of the scaffold. Micro-CT showed that magnesium scaffolds degraded mainly from the outside to inside, and new bone was ingrown following the degradation of magnesium scaffolds. The hydroxyapatite scaffold was not degraded and had fewer osteoblasts scattered on its surface. There was a significant difference in the new bone formation and scaffold bioabsorption between the two groups (9.29±1.27 vs 1.40±0.49 and 7.80±0.50 vs 0.00±0.00 mm3, respectively; P<0.05). The magnesium scaffold performed well in degradation and osteogenesis, and is a promising material for orthopedics.